Studies on the Moisture Retention Characteristics of Laterite Soils of Kerala - Thulasidharan C K (Department of Agronomy, College of Horticulture, 1983)
An experiment was conducted at the College of Horticulture during the period from April 1981 to May 1982 to study the moisture retention characteristics of the laterite soil of Kerala. Seventyfive soil samples were collected from fifteen profiles at five depths from different parts of Kerala covering Cannore, Calicut, Trichur, Kottayam and Trivandrum districts. Moisture retension studies were done at six tensions, viz., 0.3, 1, 3, 5, 10 and 15 bars. The moisture retension characteristics were correlated with the organic carbon content and texture of the soil by multiple regression analysis. The study revealed that more than 50 per cent depletion of the available water in the sieved soil occurred at less than 3 bars. The mean moisture content of sieved soil at 0.3 and 15 bars were 19.4 per cent and 25.2 per cent respectively. From the study it was also observed that the organic carbon had no significant bearing on the moisture retention characteristics of the soils studied. The content of fine fractions was found to be the determining factor which had positive influence on moisture retention. On the contrary, the effect of coarse fractions (fine and coarse sand) was negative and significant. The gravel fraction in the laterite was found to retain available water which came to the magnitude of 27 per cent of that in the sieved fraction. The content of gravel was having a strong negative influence with the moisture retention characteristics. The moisture contents at 0.3 and 15 bars including gravel were found to be 14.4 per cent and 11.3 per cent respectively on weight basis. Prediction equations were developed to determine the moisture retention at 0.3 and 15 bars of the 2 mm sieved fractions and of the soil including gravel from the contents of organic carbon and gravel and particle size distribution.